Formação em Pedagogia e universo de atuação docente nos anos iniciais - Benedita de Almeida; Clésio A. Antonio; Mafalda Nesi Francischett; Cecília Maria Ghedini; André Pereira Pedroso (Revista Diálogo Educacional, 2012)
Teacher education for the initial years of basic education, in course of Pedagogy, is the focus of this text, which weaves itself upon the relation between the teacher's profile in this stage of the basic education and the conditions of effectiveness of this education in the public university. The results come from inquiries with teachers egress from of a course of Pedagogy in a southwestern public university in Parana state. Basing itself on a historicalcultural perspective of the human development, it considers the university as a formative space for teacher's skills and it takes the relation between the teacher's education and the universe of the teacher's work as reference to present crucial issues in this field of education which request ways for the improvement of education in Brazil.